Risankizumab as induction therapy for Crohn's disease: results from the phase 3 ADVANCE and MOTIVATE induction trials. Issue 10340 (28th May 2022) - D'Haens, Geert; Panaccione, Remo; Baert, Filip; Bossuyt, Peter; Colombel, Jean-Frederic; Danese, Silvio; Dubinsky, Marla; Feagan, Brian G; Hisamatsu, Tadakazu; Lim, Allen; Lindsay, James O; Loftus, Edward V; et al.
Summary: Background: Risankizumab, an interleukin (IL)-23 p19 inhibitor, was evaluated for safety and efficacy as induction therapy in patients with moderately to severely active Crohn's disease. Methods: ADVANCE and MOTIVATE were randomised, double-masked, placebo-controlled, phase 3 induction studies. Eligible patients aged 16–80 years with moderately to severely active Crohn's disease, previously showing intolerance or inadequate response to one or more approved biologics or conventional therapy (ADVANCE) or to biologics (MOTIVATE), were randomly assigned to receive a single dose of intravenous risankizumab (600 mg or 1200 mg) or placebo (2:2:1 in ADVANCE, 1:1:1 in MOTIVATE) at weeks 0, 4, and 8. We used interactive response technology for random assignment, with stratification by number of previous failed biologics, corticosteroid use at baseline, and Simple Endoscopic Score for Crohn's disease (SES-CD). All patients and study personnel (excluding pharmacists who prepared intravenous solutions) were masked to treatment allocation throughout the study. Coprimary endpoints were clinical remission (defined by Crohn's disease activity index [CDAI] or patient-reported outcome criteria [average daily stool frequency and abdominal pain score]) and endoscopic response at week 12. The intention-to-treat population (all eligible patients who received at least one dose of study drug in the 12-week induction period) was analysed for efficacy outcomes. Safety was assessed in all patients who received at least one dose of study drug. Both trials were registered on ClinicalTrials.gov, NCT03105128 (ADVANCE) and NCT03104413 (MOTIVATE), and are now complete. Findings: Participants were enrolled between May 10, 2017, and Aug 24, 2020 (ADVANCE trial), and Dec 18, 2017 and Sept 9, 2020 (MOTIVATE trial). In ADVANCE, 931 patients were assigned to either risankizumab 600 mg (n=373), risankizumab 1200 mg (n=372), or placebo (n=186). In MOTIVATE, 618 patients were assigned to risankizumab 600 mg (n=206), risankizumab 1200 mg (n=205), or placebo (n=207). The primary analysis population comprised 850 participants in ADVANCE and 569 participants in MOTIVATE. All coprimary endpoints at week 12 were met in both trials with both doses of risankizumab (p values ≤0·0001). In ADVANCE, CDAI clinical remission rate was 45% (adjusted difference 21%, 95% CI 12–29; 152/336) with risankizumab 600 mg and 42% (17%, 8–25; 141/339) with risankizumab 1200 mg versus 25% (43/175) with placebo; stool frequency and abdominal pain score clinical remission rate was 43% (22%, 14–30; 146/336) with risankizumab 600 mg and 41% (19%, 11–27; 139/339) with risankizumab 1200 mg versus 22% (38/175) with placebo; and endoscopic response rate was 40% (28%, 21–35; 135/336) with risankizumab 600 mg and 32% (20%, 14–27; 109/339) with risankizumab 1200 mg versus 12% (21/175) with placebo. In MOTIVATE, CDAI clinical remission rate was 42% (22%, 13–31; 80/191) with risankizumab 600 mg and 40% (21%, 12–29; 77/191) with risankizumab 1200 mg versus 20% (37/187) with placebo; stool frequency and abdominal pain score clinical remission rate was 35% (15%, 6–24; 66/191) with risankizumab 600 mg and 40% (20%, 12–29; 76/191) with risankizumab 1200 mg versus 19% (36/187) with placebo; and endoscopic response rate was 29% (18%, 10–25; 55/191) with risankizumab 600 mg and 34% (23%, 15–31; 65/191) with risankizumab 1200 mg versus 11% (21/187) with placebo. The overall incidence of treatment-emergent adverse events was similar among the treatment groups in both trials. Three deaths occurred during induction (two in the placebo group [ADVANCE] and one in the risankizumab 1200 mg group [MOTIVATE]). The death in the risankizumab-treated patient was deemed unrelated to the study drug. Interpretation: Risankizumab was effective and well tolerated as induction therapy in patients with moderately to severely active Crohn's disease. Funding: AbbVie.